Вор: роман / Леонид Леонов - Леонов Леонид Максимович (Удмуртия, 1986)
Экземпляры: ф.15 (20230517) / Инвентарный номер: 62242 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: Л 47 / ББК: 84(2РОС)[Рус]{6}-444.2(2){613}